1986
DOI: 10.1002/pros.2990090211
|View full text |Cite
|
Sign up to set email alerts
|

Persistent blockade of the pituitary‐gonadal axis in patients with prostatic carcinoma during chronic administration of D‐Trp‐6‐LH‐RH

Abstract: Forty patients with stage D2 prostatic carcinoma were treated for up to 30 months with D-Trp-6-LH-RH. The analog was given s.c. once daily at a dose of 1 mg/day for the first 7 days. Subsequently, the dose was reduced to 100 micrograms/day. In follow-up studies, 30 men continued this therapy for up to 24 months. Blood samples were taken before the injection of the analog and 1, 2, 4, and 6 hours later. Serum LH, FSH, and testosterone levels were measured by RIA every month for 2 years. The initial administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…3 (2,3,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The therapy based on agonists of LH-RH avoids the cardiovascular and mammotropic side effects of estrogens and the psychological impact of orchiectomy (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). It has been suggested that treatment with [D-Trp6]LH-RH produces a higher rate of response than transcapsular orchiectomy (35).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 (2,3,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The therapy based on agonists of LH-RH avoids the cardiovascular and mammotropic side effects of estrogens and the psychological impact of orchiectomy (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). It has been suggested that treatment with [D-Trp6]LH-RH produces a higher rate of response than transcapsular orchiectomy (35).…”
mentioning
confidence: 99%
“…It has been suggested that treatment with [D-Trp6]LH-RH produces a higher rate of response than transcapsular orchiectomy (35). The use of LH-RH agonists may be the method of choice for the treatment ofprostate cancer (3,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) been used successfully for the treatment of women with endometriosis (37) and children with precocious puberty (38). However, the duration of response and the median survival time in patients with prostate cancer cannot yet be estimated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In follow-up studies, Gonzalez-Barcena and associates 45 treated 40 patients with stage D 2 prostatic carcinoma for up to 30 months with D-Trp 6 LHRH. As in the first study, the analog was given subcuta-neously once daily at a dose of 1 mg per day for the first 7 days, and subsequently the dose was reduced to 100 µg per day.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Between the beginning of the 1980s and the 2000s, multiple studies were performed using RIA investigating the castration efficacy of LHRH agonists (46,(118)(119)(120)(121)(122)(123)(124)(125)(126)(127) and one antagonist (128). Another study in that period investigated testosterone levels in surgically castrated prostate cancer patients (129).…”
Section: Early Testosterone Analysismentioning
confidence: 99%